Virtual learning environments: adoption without progression. (2017) - Sinclair, Jane; Aho, Anne-Maria
Despite widespread deployment of virtual learning environments, understanding of instructors' actual use of these systems or the reasons behind the observed patterns of behaviour is still limited. Using a qualitative approach, our work seeks to better understand staff perspectives and motivations and to generate themes for further investigation. As the initial step, we have conducted in-depth interviews with Moodle support staff from two different universities, gathering rich data on platform use and staff attitudes. The data was analysed using a coding and categorisation process to identify emergent themes. Our findings indicate a lack of progression of use and reveal several conceptual and pedagogic challenges acting as barriers to adoption or to deeper use of the environment's functionality. Exploiting further the affordances of the system is likely to necessitate reappraisal, both of current pedagogy and of one's conceptualisation of being a teacher. Themes for further exploration with teaching staff are proposed.